Effects of method of preparation and physical form on feeding value of sorghum grain to grow and finish swine - Ly, C-C; Miller, L.; Deyoe, C.W.; Phost, H.B.; Tribble, L.F. (Kansas Agricultural Experiment Station, 2011)
Sorghum grain was prepared in a hammermill with a 1/8-inch screen and by steam rolling through a fine corrugated roller mill. Each preparation was fed in meal, pellet or crumble form. The rations also contained soybean oil meal, vitamins, minerals and antibiotics. The ration contained 16 percent protein until the pigs weighed 100; 12% thereafter.
Keywords: Swine; Sorghum grain; Hammermill; Gain